Digestible lysine requirements of broilers - Bernal, LEP; Rostagno, HS; Albino, LFT; Tavernari, FC (Revista Brasileira de Ciência Avícola, 2013)
odern broilers have been submitted to continuous genetic improvement, and therefore, their nutritional requirements must be constantly updated to ensure their performance. Two experiments were carried out to evaluate different digestible lysine levels for starter (1021 days) and grower (22-35 days) phases. The experiments were carried out with male and female Cobb 500 broilers, distributed according to a randomized block experimental design in a 5x2 factorial arrangement (5 increasing digestible lysine levels x 2 sexes), totaling 10 treatments, with 8 replicates of 22 and 20 birds during the starter and grower phase, respectively. Digestible lysine levels of 1.06, 1.12, 1.18, 1.24, and 1.30 were used in the starter diets (10-21 days) and 0.9, 0.98, 1.04, 1.10, and 1.16% in the grower diets (22-35 days). Based on the statistical analyses of the evaluated performance parameters, digestible lysine requirements for maximum performance were determined as 1.22% for males and 1.24% for females in the starter phase, and 1.16% for both sexes in the grower phase. Carcass and performance results indicate that digestible lysine requirements vary with sex and evaluated production parameter. Considering the most relevant broiler production parameters, in 22- to 35-d-old males, digestible lysine requirement for breast meat yield (1.16%) was higher than those for feed conversion ratio (1.07%) and weight gain (1.05%).
Keywords: Digestible lysine; Requirement; Performance; Broiler